2014
DOI: 10.1073/pnas.1406741111
|View full text |Cite
|
Sign up to set email alerts
|

The Cap1–claudin-4 regulatory pathway is important for renal chloride reabsorption and blood pressure regulation

Abstract: The paracellular pathway through the tight junction provides an important route for transepithelial chloride reabsorption in the kidney, which regulates extracellular salt content and blood pressure. Defects in paracellular chloride reabsorption may in theory cause deregulation of blood pressure. However, there is no evidence to prove this theory or to demonstrate the in vivo role of the paracellular pathway in renal chloride handling. Here, using a tissue-specific KO approach, we have revealed a chloride tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 53 publications
6
57
1
Order By: Relevance
“…Previous studies have shown that constitutive Cldn1 inactivation in mice results in perinatal death due to loss of epidermal TJ integrity (23), while CLDN4 is also expressed in kidney and lung, and constitutive or conditional Cldn4 inactivation has been linked to urothelial hyperplasia and hydronephrosis (53), failure of chloride reabsorption (54), and susceptibility to lung injury (33). Our results thus suggest that the BBB and GL represent a coordinated double barrier to CNS entry.…”
Section: And E) In Contrast Lesions In Mgfapcre Cldn4supporting
confidence: 54%
“…Previous studies have shown that constitutive Cldn1 inactivation in mice results in perinatal death due to loss of epidermal TJ integrity (23), while CLDN4 is also expressed in kidney and lung, and constitutive or conditional Cldn4 inactivation has been linked to urothelial hyperplasia and hydronephrosis (53), failure of chloride reabsorption (54), and susceptibility to lung injury (33). Our results thus suggest that the BBB and GL represent a coordinated double barrier to CNS entry.…”
Section: And E) In Contrast Lesions In Mgfapcre Cldn4supporting
confidence: 54%
“…The mean BP in KO was 17.6 mmHg lower than in control animals (P = 0.0007) ( Table 1). To record BP in awake and unrestrained animals, sex-(male) and age-matched (12-wk-old) KO and littermate control mice were implanted with radiotelemetric transducers in the carotid artery (11). The 24-h telemetric traces showed that the mean BP in KO was consistently lower than in control animals throughout the 24-h period, with statistical significance reached for each time point (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the PHA-II mechanism in the DCT has been extensively studied, the CNT/CD's role remains largely elusive. The predominant NaCl transport pathway in the CNT/CD is through epithelial Na + channel (ENaC) mediated Na + reabsorption and electrically coupled paracellular Cl − reabsorption (also known as the chloride shunt) (10,11). WT WNK4 inhibits ENaC conductivity, whereas PHA-II-causing mutations eliminate WNK4's inhibition of ENaC, thereby promoting Na + reabsorption in the CNT/CD (12).…”
mentioning
confidence: 99%
“…The extracellular loops of claudins interact with each other to seal the cellular sheet and regulate paracellular transport between luminal and basolateral spaces (Lal-Nag and Morin, 2009). Claudin-4 has been detected in diverse epithelia, such as salivary, renal, lung, intestinal and epidermal cells (Akazawa et al, 2013;Cong et al, 2013;Gong et al, 2014;Kage et al, 2014;Shrestha et al, 2014). In rat submandibular SMIE cells, overexpression of claudin-4 increases TER and decreases the epithelial permeability of 70 kDa dextran (Michikawa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%